2014
DOI: 10.5114/amsik.2014.44590
|View full text |Cite
|
Sign up to set email alerts
|

Accidental intoxication with hydrochloric acid and hydrofluoric acid mixture

Abstract: W pracy opisano śmiertelny przypadek omyłkowego spożycia mieszaniny kwasu solnego i fluorowodorowego. Mężczyzna został przewieziony do szpitala, gdzie wdrożono prawidłowe, adekwatne do jego stanu leczenie. W trakcie hospitalizacji obserwowano liczne epizody migotania komór, z powodu których chory był wielokrotnie defibrylowany. Chory znajdował się w stanie krytycznym z narastającymi cechami wstrząsu hipowolemicznego i rozwijającej się niewydolności wielonarządowej. Następnego dnia po przyjęciu do szpitala stwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In our study the majority of complications were observed in patients after acid ingestion. Several studies have also reported less favorable outcome for acid ingestion [ 6 , 7 , 32 , 33 , 34 , 35 , 36 ]. Hydrochloric acid caused severe complications in the whole group of patients and, especially, severe complications were present in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study the majority of complications were observed in patients after acid ingestion. Several studies have also reported less favorable outcome for acid ingestion [ 6 , 7 , 32 , 33 , 34 , 35 , 36 ]. Hydrochloric acid caused severe complications in the whole group of patients and, especially, severe complications were present in the elderly group.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrochloric acid caused severe complications in the whole group of patients and, especially, severe complications were present in the elderly group. Hydrochloric acid is a widespread industrial product used in numerous countries as a rust remover, pool cleaner, drain and toilet bowl cleaner, and in other household products [ 30 , 34 , 37 ]. Severe, even fatal, intoxications were reported from several European countries [ 6 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent exposure is by cutaneous contact with the aqueous solution, no matter if the skin is intact or damaged [ 28 ], [ 29 ], [ 30 ], [ 31 ], [ 32 ]; it could also be absorbed through eyes [ 33 ], [ 34 ]. Inhalation intoxication occurs not only from exposure to hydrogen fluoride gas [ 17 ], [ 35 ], but also from vapors arising from concentrated hydrogen fluoride liquid [ 20 ], [ 36 ], while ingestion [ 14 ], [ 37 ], [ 11 ] of even a small amount of this acid is likely to produce systemic effects and may be fatal [ 13 ], [ 16 ], [ 18 ], [ 38 ], [ 39 ].…”
Section: Corrosiveness and Toxicitymentioning
confidence: 99%
“…Chronic symptoms may even occur several months after HF ingestion [ 12 ] or may persist with months after the long-time respiratory exposure [ 3 ]. Sometimes, systemic intoxication has a lethal outcome [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ].…”
Section: Introductionmentioning
confidence: 99%